Marketability and Nutritional Qualities of Some Edible Forest Insects in Benue State, Nigeria - Agbidye, F.S.; Ofuya, T.I.; Akindele, S.O. (Pakistan Journal of Nutrition, 2009)
This study investigated the marketability and nutritional qualities of four edible insect species in Benue State. Using market survey checklists, 10 out of the 23 Local Government Areas and three major towns of Benue State were covered for data collection. Proximate composition of the edible insects marketed in the study area was determined on dry weight basis. One-way ANOVA was used in analyzing the data collected. Results showed that Cirina forda Westwood had significantly the highest mean quantity per marketer of 13.2 kg. There was no significant difference in the mean quantity per marketer of Bunaea alcinoe Cram (3.5 kg), Macrotermes natalensis Haviland (1.6 kg) and Brachytrupes membranaceus Drury (0.2 kg). The proximate composition of the selected edible insects showed that the crude protein contents of the caterpillars of the emperor moths, C. forda (74.35±0.09), B. alcinoe (74.34±0.04) were significantly highest (p